Descending projections from auditory cortex to excitatory and inhibitory cells in the nucleus of the brachium of the inferior colliculus - Mellott, Jeffrey G.; Bickford, Martha E.; Schofield, Brett R. (Frontiers in Systems Neuroscience, 2014)
Descending projections from the auditory cortex (AC) terminate in subcortical auditory centers from the medial geniculate nucleus (MG) to the cochlear nucleus, allowing the AC to modulate the processing of acoustic information at many levels of the auditory system. The nucleus of the brachium of the inferior colliculus (NBIC) is a large midbrain auditory nucleus that is a target of these descending cortical projections. The NBIC is a source of several auditory projections, including an ascending projection to the MG. This ascending projection appears to originate from both excitatory and inhibitory NBIC cells, but whether the cortical projections contact either of these cell groups is unknown. In this study, we first combined retrograde tracing and immunochemistry for glutamic acid decarboxylase (GAD, a marker of GABAergic cells) to identify GABAergic and non-GABAergic NBIC projections to the MG. Our first result is that GAD-immunopositive cells constitute ~17% of the NBIC to MG projection. We then used anterograde labeling and electron microscopy to examine the AC projection to the NBIC. Our second result is that cortical boutons in the NBIC form synapses with round vesicles and asymmetric synapses, consistent with excitatory effects. Finally, we combined fluorescent anterograde labeling of corticofugal axons with immunochemistry and retrograde labeling of NBIC cells that project to the MG. These final results suggest first that AC axons contact both GAD-negative and GAD-positive NBIC cells and, second, that some of cortically-contacted cells project to the MG. Overall, the results imply that corticofugal projections can modulate both excitatory and inhibitory ascending projections from the NBIC to the auditory thalamus.